The absolute violation why torture must be prohibited - Matthews, Richard (McGill-Queen's Univ. Press, 2008)
"State torture has found an increasing number of defenders in law, philosophy, and public policy. Their defences often ignore the empirical literature on torture and thus misunderstand its nature and the damage it does, as well as accepting the illusory benefits it promises." "Richard Matthews challenges the increasing acceptability of state-sponsored torture interrogation, repudiating any possible justifications. He confronts its various supporters - ticking time bomb and tragic choice theorists, utilitarians, legal scholars - and draws from philosophy, medicine, psychiatry, survivor and torturer narratives, history, feminism, the experience of working intelligence officials, anthropology, and game theory to illustrate that no moral justification for torture can be supported."--BOOK JACKET.